2084 and the AI revolution : how artificial intelligence informs our future - Lennox, John C., 1943- (Zondervan Reflective, 2024)
"In response to recent popular accounts, scientist and philosopher John Lennox offers a Christian perspective on humanity's future with technological enhancement, bioengineering, and AI. Here is a thought-provoking, controversial, balanced, and engaging account of the problems raised by AI and the atheist conception of what it means to be human."--